Deep Learning-Based Pulmonary Nodule Screening: A Narrative Review - Abhishek Mahajan; Ujjwal Agarwal; Rajat Agrawal; Aditi Venkatesh; Shreya Shukla; K S. S. Bharadwaj; M L. V. Apparao; Vivek Pawar; Vivek Poonia (Indian Journal of Medical and Paediatric Oncology)
Given its capacity to generate three-dimensional pictures, computed tomography is the most effective means of detecting lung nodules with more excellent resolution of detected nodules. Small lung nodules can easily be overlooked on chest X-rays, making interpretation difficult. Artificial intelligence algorithms have recently demonstrated remarkable progress in medical imaging, especially with deep learning techniques such as convolutional neural networks (CNNs). CNN produces excellent results in natural image recognition and classification using abundant available data and the computational abilities of modern computers. It further reduces false-positive pulmonary nodules in medical image processing. This review article provides a detailed and inclusive review of recent advances, challenges, performance comparisons, and possible future directions for the problem of pulmonary nodule screening using deep learning methods.